Design of Web-Based Incoming and Outgoing Letter Archiving Software for the West Kalimantan Provincial Inspectorate - Julianto, Sebri (Journal of Software Engineering, Information and Communication Technology (SEICT), 2023)
The Inspectorate of West Kalimantan Province is a government agency that has the duty and responsibility to realize quality governance. The West Kalimantan Inspectorate Secretariat has a Sub-section for Administration and General Affairs which has task of managing incoming and outgoing mail. Manual recording requires a relatively long time and also creates recurring problems in terms of searching letter data. It is hoped that this filling design can be used as a system recommendation to be applied to the West Kalimantan Provincial Inspectorate in the administration and general section. The system design method in this study uses the system development life cycle (SDLC) method with the waterfall model. Data collection was carried out by observation, interview, and literature study. This research produced an information system to help manage correspondence activities. Forms created are limited to issues in creating views of incoming mail, outgoing mail, login pages, job title pages, home pages and user pages.